2015
DOI: 10.3892/ol.2015.3154
|View full text |Cite
|
Sign up to set email alerts
|

Association between LMP2 and LMP7 gene polymorphisms and the risk of gastric cancer: A case-control study

Abstract: Abstract. The integrality of low molecular weight protein (LMP)2/LMP7 function plays an important role in the processing of GC cell antigens. The purpose of the present hospital-based case-control study was to estimate the effect of polymorphisms in the LMP2 and LMP7 genes on the risk of GC. Polymerase chain reaction-restriction fragment length polymorphism analysis was used to distinguish the Arg to His substitution at codon 60 of LMP2 (LMP2-60) and the Gln to Lys substitution at codon 145 of LMP7 (LMP7-145) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
(29 reference statements)
0
17
2
Order By: Relevance
“…For example, polymorphisms within LMP7 shows a higher prevalence in gastric cancer (GC), whereas LMP2 polymorphisms, within the same cancer, were not associated with promoting GC (Ma et al, 2015). Conversely, polymorphisms within LMP2 were found to play a key role in the development of acute myeloid leukemia and multiple myelomas, whereas polymorphisms within LMP7 were not considered a risk factor (Yu et al, 2013).…”
Section: The Immunoproteasome In Antigen Presentation and Infectionsmentioning
confidence: 99%
“…For example, polymorphisms within LMP7 shows a higher prevalence in gastric cancer (GC), whereas LMP2 polymorphisms, within the same cancer, were not associated with promoting GC (Ma et al, 2015). Conversely, polymorphisms within LMP2 were found to play a key role in the development of acute myeloid leukemia and multiple myelomas, whereas polymorphisms within LMP7 were not considered a risk factor (Yu et al, 2013).…”
Section: The Immunoproteasome In Antigen Presentation and Infectionsmentioning
confidence: 99%
“…However, not all individuals exposed to such risk factors develop this disease, suggesting that genetic factors may contribute to its development. Indeed, many previous studies have reported that certain genes are involved in gastric cancer risk, includingmiR-146a, IL-17A, LMP2, LMP7, IGF1, and GSTM1 (Farahani et al, 2015;Hou and Yang, 2015;Ma et al, 2015;Wei et al, 2015;Zhang and Cui, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in mice, genetic loss of LMP7 mice causes accumulation of polyubiquitinated proteins and oxidative stress . Strikingly, several human diseases, including multiple myeloma, gastric cancer, Huntington's Disease, Alzheimer's Disease and amyotrophic lateral sclerosis, have increased IP levels or are associated with subunit polymorphisms . These observations are also hard to reconcile with the canonical role of IPs in antigen presentation.…”
Section: Introductionmentioning
confidence: 99%